Analisis Efektivitas Auditor Internal Untuk Meningkatkan Kinerja Perusahaan Dalam Perspektif Islam: Studi Kasus Pada PT. Herfinta Farm And Plantation Medan - Alvi Natzmi; Andri Soemitra (Journal Economic Excellence Ibnu Sina, 2023)
An audit is a systematic process carried out by an auditor to obtain and evaluate evidence of a company's economic events and include fairness based on predetermined standards and convey the findings obtained to interested parties. My aim in writing this article is to find out to what extent auditors play a role in improving company performance from an Islamic perspective. The method I used in this research was using qualitative research methods by means of field observations, interviews with related sources and supported by several sources such as books, journals and other documents. The results of this research are that an auditor has a vital role in the management and administrative audits in every institution or company, because with an audit, the financial system in a company will run well and will of course have an impact on improving the quality of each existing employee. at every company. So I can conclude that audits within the company must be carried out periodically to review the extent to which administrative controls have been implemented to improve company performance and to achieve predetermined goals